INFLUENCE OF SURFACE QUALITY ON THE CORROSION AND CORROSION FATIGUE BEHAVIOR OF HIGH ALLOYED STEELS EXPOSED TO DIFFERENT SALINE AQUIFER WATER ENVIRONMENTS - Pfennig, Anja; Gröber, Andre; Simkin, Roman; Kranzmann, Axel (MATTER: International Journal of Science and Technology, 2019)
Coupons of X5CrNiCuNb16-4 with different surface roughness that may be utilized as injection pipe with 16% Chromium and 0.05% Carbon (1.4542, AISI 630) were exposed for 3000 h to CO2-saturated saline aquifer water simulating the conditions in the Northern German Basin at ambient pressure and 60 °C. Additionally, corrosion fatigue experiments (ambient pressure, technically clean CO2, saline aquifer water of Stuttgart Aquifer) were performed using specimen of X46Cr13 (1.4043, AISI 420C) with regard to the influence of the roughness of technical surfaces on the number of cycles to failure at different stress amplitudes. Specimen of duplex stainless steel X2CrNiMoN22-3-2 (1.4462) for corrosion fatigue experiments were provided with technical surfaces after machining as well as polished surfaces. Results were obtained at load amplitudes ranging from 175 MPa to 325 MPa in the geothermal brine of the Northern German Basin at 98 °C. The main precipitation phases on the surface as well as within pits reveal carbonates or hydroxides such as siderite (FeCO3) and ferrous hydroxide goethite (FeOOH) independent of the original surface roughness. Corrosion rates for polished and technical surfaces were below 0.005 mm/year compared to corrosion rates of 0.035 mm/year after shot peening. Specimen with technical surfaces tested at high stress amplitudes (>275 MPa) lasted longer (cycles to failure: P50% at Sa 300 MPa=5x105) than specimen with polished surfaces (cycles to failure: P50% at Sa 300 MPa=1.5x105). This behavior is emphasized by the slope coefficient (technical surfaces k = 19.006, polished surfaces k=8.78) meaning earlier failure for polished at high stress amplitude Sa. Although rather low scatter ranges (technical surface: TN=1:1.35, polished surface: TN=1.1.95) indicate no change in failure mechanism it may be assumed that at low stress pitting is the initiating crack growth process whereas at high stress amplitudes the formation of micro cracks is reason for crack propagation and failure.